2000
DOI: 10.1021/np990366t
|View full text |Cite
|
Sign up to set email alerts
|

Excoecarins D, E, and K, from Excoecaria agallocha

Abstract: Three novel diterpenoids, excoecarins D, E, and K (1-3), were isolated from Excoecaria agallocha. The structures of 1-3 were established as 3alpha,18-dihydroxy-3beta,20-epoxybeyer-15-ene, (15R, 16S)-ent-15,16-epoxybeyeran-3-one, and ent-3beta-hydroxykaur-16-en-2-one, respectively, on the basis of extensive NMR experiments and, in the case of 1, by X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 12 publications
1
42
0
Order By: Relevance
“…The 1 H-and 13 C-NMR spectra of 1 were similar to those of excoecarin D (10) 16) which was assigned to be 3a,18-dihydroxy-3b,20-epoxybeyer-15-ene, except that the methine proton at C-2 was substituted by a hydroxyl group. This was confirmed by a heteronuclear multiple-bond coherence (HMBC) experiment (Fig.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The 1 H-and 13 C-NMR spectra of 1 were similar to those of excoecarin D (10) 16) which was assigned to be 3a,18-dihydroxy-3b,20-epoxybeyer-15-ene, except that the methine proton at C-2 was substituted by a hydroxyl group. This was confirmed by a heteronuclear multiple-bond coherence (HMBC) experiment (Fig.…”
mentioning
confidence: 71%
“…3). The optical rotation of 1 showed a negative sign, similar to that of excoecarin D. 16) Consequently, the structure of 1 was assigned to be 2a,3a,18-trihydroxy-3b,20-epoxybeyer-15-ene.…”
mentioning
confidence: 82%
“…The EtOAc fraction (110 g) was chromatographied on a silica gel column with a gradient CHCl 3 -MeOH solvent system to afford ten fractions (Fr. [1][2][3][4][5][6][7][8][9][10]. Purification of some parts of the fractions was reported in our previous report.…”
Section: Methodsmentioning
confidence: 99%
“…and 13 C-NMR signal 5,7,8) showed the presence of beyer-15-ene skeleton in the structure. So compound 1 should be composed of a (Z)-p-coumaroyl and a beyer-15-ene units through an ester linkage.…”
mentioning
confidence: 96%
“…Previous phytochemical investigation studies of E. agallocha leaves revealed that the presence of diterpenoids, triterpenoids, flavonoids, alkaloids, anthraquinone, phytosterol, fixed oil, tannin, phorbole esters, free amino acids, mucilage, glycosides, carbohydrates, and lignin [55,56]. Novel Exoecarin D, E and F diterpenoid from Leaves of E. agallocha and their structure depicted as 3α,18-dihydroxy-3β,20-epoxybeyer-15-ene, (15R,16S)-ent-15,16-epoxybeyeran-3-one and ent-3β-hydroxykaur-16-en-2-one using NMR and X-ray analytical techniques [57]. Additionally, 14-taraxeren-3-one, dibutyl phthalate, phaeophytin A, betulin, beta rosasterol, betulinic aicd oleanolic and ursolic acid also identified from EA [58].…”
Section: Chemical Composition Of E Agallochamentioning
confidence: 99%